Treatment of malignant tumors of the oral cavity - state of the art - Waldfahrer, F... (Radiology and oncology (Ljubljana), 1997)
In the past decades minimally invasive surgery and multimodal treatment strategies have gained in importance in the treatment of oral cancer as well as elsewhere. Within this concept, the primary tumor is resected enorally whenever possible, especially by carbon dioxide laser. The regional lymphaticsare treated preferentially with functional neck dissection, preserving the sternocleido-mastoid muscle, accessory nerve and internal jugular vein. As a part of this multimodal treatment concept, percutaneous andinterstitial radiotherapy was of great significance. Interstitial radiotherapy with iridium-seeds in the region of the (removed) primary tumor allows, on the one hand, local application of a high radiation dose and, on the other, protection of the surrounding tissues. The neck may be irradiated percutoneusly, if necessary. By using this concept, extensive surgery with disfiguring defects, impaired swallowing, speech and chewing, and the necessity of reconstruction measures can be avoided in many cases with equallygood treatment results and even improved quality of life. Tumours whichcannot be resected by organ sparing surgery, will be treated by simultaneous radiochemotherapy. This report discusses the results of treating of 614 patients with oral cancer admitted to the Deparment of otolaryngology. Head and Neck Surgery, University Erlangen-Nueremberg, during the period of 1970 to 1994.
Keywords: Combined modality therapy; Mouth neoplasms; Survival analysis; Therapy